2007
DOI: 10.1029/2006je002781
|View full text |Cite
|
Sign up to set email alerts
|

Convection in ice I shells and mantles with self‐consistent grain size

Abstract: [1] The viscosity of ice I is grain size dependent for temperature and stress conditions appropriate for ice I shells and mantles of large and midsized icy satellites. Satellite thermal evolution, heat flux, critical shell thickness for convection, brittle/ductile transition temperature, and potential for surface deformation are therefore grain size dependent. Using measured grain sizes from terrestrial ice sheets experiencing temperature and strain rate conditions similar to convecting ice shells in icy satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 47 publications
3
111
0
Order By: Relevance
“…These observations have revealed that the grain size within terrestrial ice sheets is controlled not only by the temperature depen dent normal grain growth process but also by the concen tration of non water ice impurities (e.g., Durand et al, 2006) and the recrystallization due to strain accumulation (e.g., De La Chapelle et al, 1998). In a recent study, these results were used to set constraints for the grain size de pendent convection model for ice shells and mantles (Barr and McKinnon, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…These observations have revealed that the grain size within terrestrial ice sheets is controlled not only by the temperature depen dent normal grain growth process but also by the concen tration of non water ice impurities (e.g., Durand et al, 2006) and the recrystallization due to strain accumulation (e.g., De La Chapelle et al, 1998). In a recent study, these results were used to set constraints for the grain size de pendent convection model for ice shells and mantles (Barr and McKinnon, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…All three creep regimes are implemented to calculate a range 220 in T b. Only the grain boundary sliding (GBS) regime is dependent on grain size, in which a range 221 from 1mm to 10cm (appropriate for a convecting ice mantle in which grain size has reached 222 equilibrium) was used (Barr and McKinnon 2007). 223 T b also depends on the strain rate ε , the gas constant R, grain size d, and the shear 224 modulus µ, which is calculated from v and E used in equation (1).…”
mentioning
confidence: 99%
“…This effect is poorly known, but preliminary works suggest that grain sizes in equilibrium with convection in icy satellites could vary largely, both vertically and laterally, and to be relatively large, between one millimeter and several centimeters (Barr and McKinnon, 2006;Tobie et al, 2006). These works do not account for the effect of tidal stresses: if tidal stresses in the ice shell of Europa, typically of ∼0.1 MPa (Greenberg et al, 1998), are considered, the grain size in dynamic equilibrium would be ∼4 mm (Barr and McKinnon, 2006). These grain sizes are mostly beyond the preferred range obtained by the present study for grain boundary sliding, and implies freezing of the entire water crust for diffusion creep.…”
Section: Discussionmentioning
confidence: 99%
“…(1)- (3) are appropriate for homogeneous heat dissipation rates. The grain size could similarly be heterogeneous in the ice shell, due to variations in ice contaminants or to differential temperature-enhanced crystal growth or dynamical re-crystallization (Tobie et al, 2006;Barr and McKinnon, 2006). Although these effects can be incorporated to numerical models, parameterized formalisms have the advantage of more easily to explore of the influence of varying the rheology on the convective heat transfer.…”
Section: Steady-state Tidally Heated Convection In the Ice Shellmentioning
confidence: 99%
See 1 more Smart Citation